2006
DOI: 10.1207/s15326985ep4102_4
|View full text |Cite
|
Sign up to set email alerts
|

The Four-Phase Model of Interest Development

Abstract: Building on and extending existing research, this article proposes a 4-phase model of interest development. The model describes 4 phases in the development and deepening of learner interest: triggered situational interest, maintained situational interest, emerging (less-developed) individual interest, and well-developed individual interest. Affective as well as cognitive factors are considered. Educational implications of the proposed model are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

146
3,004
3
144

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 3,114 publications
(3,522 citation statements)
references
References 122 publications
146
3,004
3
144
Order By: Relevance
“…Therefore, our findings-and our broader methodological approach to examining TUTs during learning-are quite compatible with feed-forward-and-feedback models of interest and engagement: Traits, habits, interests and abilities affect momentary motivations to learn, and these then create emotional and cognitive states (including focused or distracted attention), which in turn act as mediators to affect learning, which may then alter those original traits, habits, interests, and abilities (e.g., Hidi, 1990Hidi, , 1995Hidi & Reninger, 2006;Schiefele, 1991).…”
Section: Issues Of Causalitymentioning
confidence: 96%
“…Therefore, our findings-and our broader methodological approach to examining TUTs during learning-are quite compatible with feed-forward-and-feedback models of interest and engagement: Traits, habits, interests and abilities affect momentary motivations to learn, and these then create emotional and cognitive states (including focused or distracted attention), which in turn act as mediators to affect learning, which may then alter those original traits, habits, interests, and abilities (e.g., Hidi, 1990Hidi, , 1995Hidi & Reninger, 2006;Schiefele, 1991).…”
Section: Issues Of Causalitymentioning
confidence: 96%
“…The interest component includes two theoretically distinct constructs that have been identified by researchers: situational interest and individual interest (Hidi & Renninger, 2006). Situational interest refers to immediate, short-term enjoyment of instructional activities, whereas individual interest refers to more enduring internally activated personal values about a topic.…”
Section: Components Of the Music Modelmentioning
confidence: 99%
“…Instructors can create situational interest by designing instruction and coursework that incorporates novelty, social interaction, games, humor, surprising information, and/or that engenders emotions (Bergin, 1999). Instructors can develop students' individual interest in a topic by providing opportunities for them to become more knowledgeable about the topic and by helping them understand its value (Hidi & Renninger, 2006).…”
Section: Components Of the Music Modelmentioning
confidence: 99%
“…Most authors emphasize the subject specificity of interest and self-efficacy (Caprara, Vecchione, Alessandri, Gerbino, & Barbaranelli, 2011;Hidi, 2006;Hidi & Renninger, 2006). In our study, we measured them with regard to specific contexts, and also found interest to be the strongest positive predictor of success in both subjects.…”
mentioning
confidence: 54%
“…Furthermore, interest also includes positive feelings for the subject and the perception of the learning content's importance for an individual. This is also reflected in longer learning time (Alexander, Murphy, Woods, Duhon, & Parker, 1997), in the activation of deep information processing strategies (Schiefele, 2001) and in enabling the connections with previous knowledge, which all lead to a better understanding of the learning material and higher achievement (Hidi & Renninger, 2006). The students' subject specific self-efficacy was an important positive predictor of academic achievement in both subjects.…”
mentioning
confidence: 99%